The Determining factors of the transparency of electronic governments in the disclosure of economic-financial information: Case of Central America - Vargas Díaz, César Daniel (2022)
Information and Communication Technologies, and specifically the Internet have enabled governments to maintain a permanent channel of communication with its citizens, by which it seeks greater participation by them and improved transparency and accountability, thereby reducing possibilities for corruption. In this context, the objective of this research is twofold: On one hand, assessing the degree of public economic and financial information that the central governments of the countries of Central America disseminate through their websites, and on the other, identifying environmental factors that may be associated with the level of public financial information disclosed through the Internet.